Avaliação dos serviços de saúde bucal na Estratégia Saúde da Família: aplicação do PCATOOL-Brasil a cirurgiões-dentistas em Araguaína - TO - Paulo, Sandro Rogério Cardoso de (Universidade Federal do Tocantins, 2024)
Introduction: The evaluation of oral health in Primary Health Care (PHC) is fundamental, as it promotes health, prevents diseases, reduces costs and guarantees a comprehensive approach to health. Objective: To evaluate the quality of oral health in the SUS through the presence and extent of PHC attributes in the municipality of Araguaína, Tocantins, from the perspective of dental surgeons (DS) Methods: A descriptive, cross-sectional and quantitative study that evaluated PHC from October to November 2023, from the perspective of DSs in PHC in Araguaína (TO). The PCATool Brazil Oral Health, in its extended version for oral health professionals, was used to measure the extent of PHC attributes, using a likert scale with 1 to 4 values and an additional option of 9 (“I don't know” / “I don't remember”), in which scores above 6.6 suggest greater presence and extent of the attributes of values ranging from 0 to 10. Two structured questionnaires with closed answers were applied to 34 DCs: one to categorize the profile of the participants and the other to evaluate PHC from the perspective of the DC by PCATool, using WhatsApp and Google tools. Results: Of the 34 volunteer DCs from Araguaína, there was a predominance of women (73.5%) and a median age of 37 years. The majority declared themselves white (52.9%) and married (50%). The average time in the profession was 9.4 years, with the majority working mainly in PHC and having no other job. Half were permanent employees and the other on a temporary contract. The majority have started specializing, mainly in areas of dentistry. Regarding the evaluation of PHC by the PCATool: of the 9 PHC components evaluated by the DCs, three had scores below 6.6: Accessibility (mean= 5.60), Community Orientation (mean= 6.15) and Cultural Competence (mean= 5.86). The component with the highest average was Comprehensiveness, rated at 8.93. The Essential Score was 7.43, while the General PHC Score was 7.07. Both scores were considered high. With the results, a Technical Research Report (RTP) was produced which will be presented at congresses, published in a scientific journal and made available to the Araguaína Municipal Health Department. Conclusion: The DCs evaluated PHC with an average score of 7.07, indicating high overall quality, according to the PCATool Brazil criteria. However, the presence of attributes in the Accessibility, Community Orientation and Cultural Competence components were lower and require intervention by management with a view to adapting these attributes (≤ 6.6). There was no statistically significant association between the individual characteristics of the interviewees and their perception of the quality of PHC. This study provides data on PHC guidance by the DCs of Araguaína's UBS, highlighting the best and those in need of improvement. This allows more assertive actions to be planned, integrating managers and professionals to strengthen PHC and promote greater community participation in work processes. This TCM is the result of the stricto sensu Professional Master's Degree Program in Family Health (PROFSAUDE).